2018
DOI: 10.1007/s11199-018-0955-z
|View full text |Cite
|
Sign up to set email alerts
|

Pink for Girls, Red for Boys, and Blue for Both Genders: Colour Preferences in Children and Adults

Abstract: z. This article may be used for non-commercial purposes in accordance with Springer Link Terms and Conditions for Use of Self-Archived Versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
3
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 79 publications
3
79
3
2
Order By: Relevance
“…The RGB values are presented on the screen together with the number of clicks taken to arrive at the final color and the time it took from the first click to the final color choice (also see Refs. 60 and 61 and https://www2.unil.ch/onlinepsylab/ColourPicker/html/colorpicker.html).…”
Section: Methodsmentioning
confidence: 99%
“…The RGB values are presented on the screen together with the number of clicks taken to arrive at the final color and the time it took from the first click to the final color choice (also see Refs. 60 and 61 and https://www2.unil.ch/onlinepsylab/ColourPicker/html/colorpicker.html).…”
Section: Methodsmentioning
confidence: 99%
“…This could be due to social learning from a young age of gender-stereotyped colors where society has displayed pink for girls and blue for boys, which could influence color preferences. 45,46 The choice for the color blue could indicate the color's association with masculinity. Women not wanting to see men wear magenta might be due to the colors genderstereotyped association with femininity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a global shift toward gender fluidity and gender equality. 17,46 It could be that women avoid red due to not wanting to be treated like a sexual object and instead chose a different color in order to promote gender equality. 46 However, scaling values showed that yellow was the preferred color to wear with denim bottoms by the female participants, indicating that other influences are affecting preferences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations